A CRITICAL STUDY ON HISTORY AND EVOLUTION OF MEDICINE REGULATION IN INDIA - B.Mughundhan , B.Mughundhan (International Journal of Advanced Science and Technology, 2020)
Every government has the responsibility to provide access to the safe, effective, and quality medication to its people. Therefore it enacts specific Laws to regulate every aspect of the drugs, i.e, manufacture, sale, distribution, and clinical research in humans. Every country has its own regulatory authority, which is responsible to enforce the rules and regulations and issue the guidelines to regulate the drug development, licensing, and registration. India has emerged as one of the leading markets for pharmaceutical products increase in the private healthcare infrastructure, and inclusion of newer technologies have been taken place when compared to other countries. The primary objective of this research is to study the medicine regulations in India and to identify the functions of drug enquiry committee. And the secondary objective of this research is to analyse the drug regulatory agencies in India. The researcher has followed the empirical with the convenient sampling method. The study used primary data which has been collected from 206 respondents with convenient. This study found that the Indian regulatory agency still have much to learn and realise the need for availability of safe medication in the public domain. There is a need to introduce new updated dynamic monitoring tools such as adverse events reporting system inbuilt in its website and risk evaluation and mitigation strategies by the pharmaceutical companies as needed by FDA and the  results observed from the analysis of the study is that the medical  regulations in India is functioning well and good and providing safe medication to all the peoples of India.